﻿Analysis of carboxylic acids of Astragalus dasyanthus Pall. herb - Olha Khvorost; Yevheniia Zudova; Liliia Budniak; Liudmyla Slobodianiuk; Hanna Kramar; Olha Palamarchuk; Anna Ocheretniuk (Pensoft Publishers, 2023)
One of the fundamental issues in modern pharmacy is the expansion of the range of medications based on plant-derived raw materials with specific targeted effects. An example of such a plant is the woolly-flowered milkvetch (Astragalus dasyanthus Pall.). This perennial herbaceous medicinal plant belongs to the Fabaceae family and is listed in the Red Book of Europe. Astragalus dasyanthus Pall. is cultivated for pharmaceutical purposes. The herb of a plant exhibits sedative, cardiotonic, hypotensive, and diuretic effects, as well as hepatoprotective and antioxidant properties. The herb of Astragalus dasyanthus Pall. contains polysaccharides (arabinose, bassorin), flavonoids (quercetin, kaempferol), glycyrrhizin, starch, and triterpenoid saponins, which contribute to the broad spectrum of the plant's pharmacological activity. Continuing the investigation of this plant, it is advisable to study the qualitative and quantitative composition of organic and fatty acids. By the HPLC method, the following organic acids were identified and determined quantitative content: tartaric (8.68 mg/g), citric (7.69 mg/g), oxalic (6.90 mg/g), succinic (5.01 mg/g), isocitric (1.30 mg/g), and malic (0.49 mg/g). The saturated and unsaturated fatty acids were determined by the GC/MS method. The Astragalus dasyanthus Pall. herb contained seven fatty acids. High concentrations of fatty acids such as pentadecanoic acid (4.16 mg/g), linoleic acid (1.73 mg/g), and stearic acid (1.14 mg/g) predominate in woolly-flowered milkvetch. The character of many processes in which these organic and fatty acids take part may be associated with the medicinal properties of this plant pursuant to its use in medicine and, therefore, may contribute to the insight into its therapeutic properties.